Five little monkeys sitting in a tree - Christelow, Eileen (New York : Houghton mifflin, 1991)
Five little monkeys sitting in a tree discover, one by one that it is unwise to tease Mr. Crocodile.
Keywords: Counting; Crocodile -- fiction; Monkeys -- fiction